(NpITANNQ L)QÆTERATUROZNAWSTWA (B:s)E (NNAUK(B. (NZB(B.s (NwIP(B. 74 /s - (N~ERN)QÆW(B. (NNAC(B. (NUN(B-(NT ÆM(B. (N`RÆQ fEDXKOWI^As)E ((N~ERN)QÆWCÆ (B:s)E [(NB(B. (NW(B.] ;s, 2007)
(NwIPUSK M)QÆSTITX ZAGALXNOTEORETI^NÆ TA ÆSTORIKO(B-(NLÆTERATURNÆ STATTÆ(B, (NROZDÆLENÆ ZA RUBRIKAMI (B"(NpOETIKA(B", "(NvANROLOGÆQ(B", "(NwÆR[OZNAWSTWO(B", "(NdISKUS(B", "(NgERMENEWTIKA(B, (NRECEPCÆQ(B, Æ(NNTERPRETACÆQ(B", "(NmETODOLOGÆQ(B". (NpORU[ENÆ W STATTQH LÆTERATUROZNAW^Æ PROBLEMI GRUNTU@TXSQ NA UKRAÇNSXKOMOWNOMU(B, (NROSÆJSXKOMOWNOMU(B, (NANGLOMOWNOMU(B, (NNÆMECXKOMOWNOMU TA FRANKOMOWNOMU MATERÆALÆ(B.s)E
Keywords: (Nl)QÆTERATUROZNAWSTWOs)E -- (NzB)QÆRNIKI(B.s)E